Time Perspective and Age: A Review of Age Associated Differences - Laureiro-Martinez, Daniella; Trujillo, Carlos A.; Unda, Juliana (Frontiers in Psychology, 2017)
We investigate the relationship between age and the five dimensions of time perspective measured by the Zimbardo Time Perspective Inventory (ZTPI) (past negative, past positive, present hedonistic, present fatalistic and future). Time perspective is related to well-being, decision-making, level of development, and many other psychological issues. Hence, the existence of a systematic relationship between time perspective and age should be considered in all studies for which time is a relevant variable. However, no specific research about it has been conducted. Adapting meta-analytical techniques, we collected 407 papers that referenced the ZTPI between 2001 and 2015. From those, 72 studies met our inclusion criteria. They include 29,815 participants from 19 countries whose age spans most phases of adulthood (from 13.5 to 75.5 years, mean 28.7). We found that present hedonistic and past negative dimensions are negatively related to aging with partial eta squared effect sizes of roughly .15. Our results have implications for the design of studies related to time as our findings highlight the importance of taking into account the differences associated with age.